Behavior of cement-stabilized fiber-reinforced pond ash, rice husk ash–soil mixtures. Issue 3 (June 2016) - Kumar, Arvind; Gupta, Deepak
Abstract: In order to study the effect of addition of rice husk ash, pond ash, cement and fiber on the compaction and strength behavior of clay, a series of tests were performed. Modified proctor tests were conducted to evaluate the compaction behavior, while unconfined compression tests (UCS) and split tensile strength (STS) tests were conducted to evaluate the strength properties of clay. For testing purpose specimens were prepared with different amount of admixtures. Pond ash (PA) and rice husk ash were added to clayey soil at ranges of 30–45% and 5–20%, respectively. Polypropylene fibers of length 6 mm and 12 mm are used in this study with different contents as 0, 0.5, 1.0 and 1.5% by dry weight of mix whereas cement contents used are 0, 2 and 4%. To study the effect of curing on strength property, the specimens were cured for 7, 14, and 28 days and tested. Test results have shown that the maximum dry density decreases and optimum moisture content increases with the addition of admixtures, but fiber inclusion have marginal effect. The results shows that the inclusion of fiber reinforcement within un-cemented and cemented soil caused an increase in the UCS, STS and axial strain at failure, decreased the stiffness and the loss of post-peak strength, and changed the cemented soil brittle behavior to a more ductile one. Strength of clay improves by the addition of admixtures and fibers. The study has shown that combination of clay, RHA, PA, cement and fiber can be used as light weight fill material in different structures like embankment, retaining wall etc.